Penggunaan Draping Bedah Anti Mikroba untuk Mencegah Kontaminasi Selama Pembedahan - Nugraha, Bambang Aditya; Rahmayani, Melly; Saragih, Dewi Rasmita; Ramdhanie, Gusgus Ghraha (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the efficacy of using antimicrobial surgical draping on surgical area contamination. The research method used is a narrative review of the database used. The search engine used is Google Scholar. Articles based on the criteria include, published between 2020-2024, there are full manuscripts, primary research (RCT, Cross-sectional, retrospective, and cohort) in Indonesian and English. The article database uses Science Direct, EBSCO-CINAHL, and Pubmed. The keywords used are surgical draping, antimicrobial, and contamination. The study results showed 33 articles (CINAHL), 90 articles from Science Direct, and 271 articles from Pubmed, but only nine articles were the focus of the study. This study concludes that antimicrobial drapes can prevent contamination in the surgical area by preventing transmission and antibacterial. Nurses are advised to conduct further research on the types and characteristics of microbes before using antimicrobial surgical drapes. Keywords: Antimicrobial, Surgical Draping, Contamination